Effects of 8-week alkaline diet and aerobic exercise on body composition, aerobic performance, and lipid profiles in sedentary women - Yalcinkaya, Nehir; Isik, Ozkan; Beyleroglu, Malik; Erdogdu, Dogan; Cicek, Guner; Novak, Dario (Frontiers in Nutrition, 2024)
Background: Diet composition can affect systemic pH and acid-base regulation, which may in turn influence exercise performance.Purpose: It was aimed to determine the effects of the alkaline diet and eight weeks of aerobic exercises on body composition, aerobic performance, and blood lipid profiles in sedentary women.Methods: Thirty-two sedentary women participated in the study voluntarily. The research was designed with a true-experimental design and the participants were divided into four different groups as the control group, aerobic exercise group, alkaline diet group, and alkaline diet + aerobic exercise group. The body compositions, aerobic exercise performances, and lipid profiles of sedentary women were measured as pre-test and post-test. In the analysis of the obtained data, One-Way ANOVA with Bonferroni post-hoc test was used.It was observed that the alkaline diet consumed with eight weeks of aerobic exercises caused a 5.17% decrease in BMI and an increase of 42.07% and 37.62% in VO2max and aerobic test durations, respectively (p< 0.05). In addition, when lipid profiles were examined, it was determined that there was no statistically significant difference in HDL-C levels (p> 0.05). Despite that, there were statistically significant differences in TG and LDL-C levels (p< 0.05). According to this result, it was determined that there was a decrease in TG and LDL-C levels by 37.61% and 20.24%, respectively. This is a provisional file, not the final typeset article Conclusion: An alkaline diet consumed with eight weeks of aerobic exercises in sedentary women has positive effects on improving body composition, aerobic exercise performances, and TG and LDL-C levels.